Long-term hemodynamic response of carvedilol and simvastatin in compensated versus decompensated chronic liver disease with portal hypertension - Nazir, Shaheen; Wani, Zeeshan Ahmed; Ahmad, Afaq; Asif Iqbal; Hussain, Altaf (Asian Journal of Medical Sciences, 2024)
Background: A combination of carvedilol and Simvastatin have recognized their role as rescue therapy for carvedilol non-responders in chronic liver disease (CLD)-associated portal hypertension. However, there are scarce data regarding its role in specific subclasses, and stratification of response according to the computed tomographic perfusion (CTP) score has never been seen before. Aims and Objective: (1) To compare hemodynamic response and side effects of a combination therapy in decompensated and compensated patients. (2) Stratify the effect of combination therapy according to CTP score. Materials and Methods: In 102 consecutive patients of CLD with esophageal varices, the hepatic venous pressure gradient was measured at baseline and after 3 months of dose optimization of carvedilol. Simvastatin was added to non-responders and hemodynamics repeated at 1 month of dual therapy. The response of compensated CLD was compared with decompensated patients and was stratified as per the CTP on follow-up. Results: Overall, out of 43 compensated patients, 21 responded acutely and response increased to 29 (67.44%) at 3 months. While 31 of 59 (52.54%) decompensated patients responded acutely but dose escalation did not increase response significantly after 3 months. The addition of Simvastatin did increase the response, although side effects were more in decompensated group. The addition of Simvastatin also decreased decompensation in the high-risk compensated group and maintained their MELD.Na. Conclusion: Response in compensated CLD patients was more than in decompensated patients; however, it was statistically insignificant. Attrition was more in patients with CTP >10 due to drug intolerance, side effects, or deaths.